2018
DOI: 10.2471/blt.17.201343
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of tuberculosis prevention for exposed children, Burkina Faso

Abstract: ObjectiveTo develop and test a simple system for recording and reporting the diagnosis and treatment of latent tuberculosis infection and to compare the effects of passive and active tracing of child contacts on indicators of such infection.MethodsWe revised Burkina Faso’s latent tuberculosis infection register and quarterly tuberculosis reporting form. Subsequently, coverage of the routine screening of contacts, who were younger than five years, for active tuberculosis and the corresponding percentages of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In addition to counselling of the index patient, arrangements should be made to counsel contacts before starting TPT. -Preferably, the health provider (trained CHW or professional health provider) conducting the contact investigation should visit the home or workplace of the index patient; conduct interviews and underscore the importance of identifying and evaluating contacts; perform symptom screening and documentation; gather more accurate information about the likely intensity and duration of exposure; and ensure all symptomatic contacts are referred for further evaluation and treatment decision and all asymptomatic contacts are assessed for TPT eligibility (see Box 2.3) (20). Home visits may need to be done outside working hours since contacts may be at work or school during these times.…”
Section: Implement Contact Investigation As Followsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to counselling of the index patient, arrangements should be made to counsel contacts before starting TPT. -Preferably, the health provider (trained CHW or professional health provider) conducting the contact investigation should visit the home or workplace of the index patient; conduct interviews and underscore the importance of identifying and evaluating contacts; perform symptom screening and documentation; gather more accurate information about the likely intensity and duration of exposure; and ensure all symptomatic contacts are referred for further evaluation and treatment decision and all asymptomatic contacts are assessed for TPT eligibility (see Box 2.3) (20). Home visits may need to be done outside working hours since contacts may be at work or school during these times.…”
Section: Implement Contact Investigation As Followsmentioning
confidence: 99%
“…Once on MDR/RR-TB treatment, children and adolescents must be monitored regularly to evaluate their response to treatment; identify treatment failure early; monitor for adverse events; and provide adherence, psychosocial and financial support to children and their caregivers. 20 A delamanid 25 mg dispersible tablet was not available at the time of the guideline development group meeting in May-June 2021, but it has since become available and is now listed in the GDF medicines catalogue (http://stoptb.org/assets/documents/gdf/drugsupply/ GDFMedicinesCatalog.pdf ). 21 Taneja R, Nahata MC, Scarim J, et al Stable sugar and sugar-free bedaquiline suspensions: practical implementation of pediatric dosing in the field.…”
Section: Monitoring Of Children and Adolescents On Multidrugresistant...mentioning
confidence: 99%
“…Examples include projects to increase rifapentine access for people living with HIV and child contacts <5 years old 156 ; that test and scale novel approaches to TB diagnostics and retention in care 157 ; and that use the TB infection care cascade as a framework to identify stepspecific, locally tailored interventions to improve retention. 42 43 158 Additional studies to improve TPT initiation among child contacts in LMIC have shown promising results of socioeconomic support, 148 enhanced contact investigation procedures 48 and multilevel community interventions. 159 Our analysis suggests several theory-based and methodological strategies to strengthen future research and programme implementation to improve retention BMJ Global Health in the TB infection care cascade.…”
Section: Barriers and Facilitators Of Treatment Completionmentioning
confidence: 99%